Recurrent episodes of jaundice in a young man with Dubin-Jhonson syndrome - Wadud, Md Abdul; Ul Azim, Muhammed Arshad; Siddique, Ashfaque Ahmed; Kabir, Md Anwarul (BIRDEM Medical Journal, 2021)
Dubin-Johnson syndrome is a rare inherited disorder associated with a defect in the ability of hepatocytes to secrete conjugated bilirubin into bile. Patients usually present with chronic or recurrent attacks of jaundice with conjugated hyperbilirubinemia. A dark pigment accumulates in the liver,which is responsible for itscharacteristic black color.It is a benign condition with a normal life expectancy and no specific treatment is required. We report a case of Dubin-Johnson syndrome in a 20-year-old man with recurrent episodes of jaundice, whose laboratory data revealed a mild conjugated hyperbilirubinemia, remaining liver function tests were normal and diagnosis was confirmed by the presence of dark brown pigment on microscopy of liver biopsy. BIRDEM Med J 2021; 11(3): 235-238